Assessing the short-term hematological and pulmonary effects of air pollution: a cross-sectional study in a Turkish urban setting - Mehmet Kılınçer; Ersan Gürsoy (BMC Public Health)
Abstract Background Air pollution has become a significant global public health concern, with evidence linking it to various adverse health outcomes, including respiratory and cardiovascular diseases. While numerous studies have investigated the effects of these particulate and gaseous pollutants on both healthy individuals and patients, further research is needed to clarify the short-term hematological and pulmonary responses in individuals without underlying health conditions. This study aims to explore the relationship between air quality, hematological parameters, and pulmonary function in a healthy population in Turkey. Methods This cross-sectional study included 326 healthy, non-smoking adults aged 18–65 years. Air Quality Index (AQI) data for the examination day and the preceding 5 days were collected. Hematological parameters and pulmonary function tests were analyzed. Spearman and Pearson correlation tests were used to compare numerical variables. Group comparisons were conducted using the independent samples t-test and Mann-Whitney U test. Results The mean AQI on the day of the medical visit was 68.20, indicating moderate air quality. Significant negative correlations were observed between AQI and hematological parameters, including leukocyte (r = -0.111, p = 0.046), lymphocyte (r = -0.134, p = 0.016), and platelet counts (r = -0.141, p = 0.011). Similar negative correlations were found for the 5-day average AQI. For pulmonary parameters, AQI was negatively correlated with FEF50% (r = -0.172, p = 0.002), FEF25% (r = -0.140, p = 0.012), FEV1/FVC% (r = -0.125, p = 0.024), and FEF75% (r = -0.124, p = 0.025). Conclusion Short-term exposure to moderate air pollution significantly impacts hematological parameters and specific pulmonary function indices, even in healthy individuals. These findings emphasize the importance of continuous air quality monitoring and public health interventions to mitigate the health risks of air pollution.